Efektivitas Pemanfaatan Media Online terhadap Partisipasi Mahasiswa dalam Kegiatan Sosial yang Berorientasi Lingkungan - Emanuel Hanoe; Erlin Fatima Halek; Antonius T. T. Ruron; Yeremias Binsasi (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2026)
The presence of technology as a manifestation of the development of human resource potential, especially social media that can be used to communicate, disseminate information. Students as agents of change, are the group most vulnerable to internet dependence and utilize social media as the main tool for communication, participation in social and environmental actions. The purpose of this study was to determine student participation in environmentally oriented social activities. The research method used a qualitative descriptive approach. Qualitative descriptive data analysis techniques with data reduction, interpretation and verification stages. The results of observations found problems in the Biology Education study program in the field of science and the environment experiencing a decline in terms of quality. Student involvement in social actions as agents of change has not been seen in overcoming environmental problems. The low participation of students in environmental activities in the community, such as conservation activities, tree planting, environmental cleanups or environmental campaigns due to lack of motivation, social interaction and understanding of science/environmental learning. Types of environmental activities known by students and practiced in organizational or group activities such as: urban waste management, the use of chemical pesticides, drought and environmentally friendly schools. Online media used by students to socialize environmental campaign activities such as using YouTube, Instagram and Facebook.